PEMBELAJARAN DIGITAL STORYTELLING SEBAGAI STRATEGI INOVATIF DALAM MENINGKATKAN ABAD KE-21 - Tekla Galla Manase; Nur Fadhilah Murtadir; Firdaus W Suhaeb (STKIP Subang, 2026)
The development of digital technology has driven a transformation in learning practices at various levels of education. One emerging innovative approach is digital storytelling, a learning method that integrates narrative with digital technology. This article aims to analyze the role of digital storytelling in improving the quality of learning and students' 21st-century competencies. The method used is a literature study by reviewing various relevant scientific sources. The results of the study indicate that digital storytelling can improve critical thinking skills, creativity, communication, and digital literacy. Furthermore, this method also increases student motivation and engagement in the learning process. However, its implementation still faces several challenges, such as limited technological facilities and educators' digital competencies. Therefore, an appropriate strategy is needed to optimize its benefits.